Teknik Diagnostik dan Staging Melanoma Maligna Kutaneus - Rudi Chandra (Cermin Dunia Kedokteran, 2020)
Melanoma maligna merupakan keganasan sel-sel penghasil pigmen (melanosit) yang terletak terutama di kulit. Tujuan setiap alat diagnostik adalah deteksi dini dan membedakan lesi jinak dan ganas, dengan sensitivitas dan spesifisitas tinggi. Diagnosis melanoma klinis dapat menggunakan Glasgow 7-point checklist, checklist ABCD, total-body photography, dan dermoskopi. Diagnosis histopatologi merupakan pemeriksaan baku emas untuk diagnosis. Diagnosis molekular dengan menilai status mutasi BRAF V600, MEK, NRAS, dan CKIT. Sedangkan teknik staging TNM menggunakan modalitas pencitraan lanjutan dengan kontras intravena, seperti computed tomography (CT) atau fluorodeoxyglucose (FDG)-based positron emission tomography (PET) CT scan, dan pemeriksaan sentinel nodus lymphatic.Malignant melanoma is a malignancy in pigments producing cells (melanocytes), located mainly in the skin. The aim of each diagnostic tool is early detection and differentiating benign and malignant lesions with high sensitivity and specificity. Clinical diagnosis can use the Glasgow 7-point checklist, ABCD checklist, total-body photography, and dermoscopy. Histopathological examination is a gold standard for diagnosis. Molecular diagnosis is done by assessing the status of mutations of BRAF V600, MEK, NRAS, and CKIT. Diagnostic techniques in melanoma TNM staging system use advanced imaging modalities with intravenous contrast, such as computed tomography (CT) or fluorodeoxyglucose (FDG)-based positron emission tomography (PET) CT scans, and examination of sentinel lymphatic lymph nodes. Rudi Chandra.